POSSIBILITIES OF USING CREATIVE STRATEGIES OF HEURISTIC CHARACTERS IN FORMING PROFESSIONAL COMPETENCES OF FUTURE TEACHERS - Qodirov Gayrat Uroqboyevich (International Scientific and Current Research Conferences, 2023)
this article examines the possibilities of using heuristic strategies to form professional competencies in future teachers. It has been analyzed that heuristic strategies are a productive pedagogical tool for developing professional competence in future teachers. In the process of choosing a new strategy, the principle of self-management of the student's personality and the formation of competences to always approach the processes with a new perspective are given.